Tinjauan Antropometri Kursi dan Meja Makan pada Restoran 4 Fingers Crispy Chicken - Irwansyah, Irwansyah (Waca Cipta Ruang, 2019)
This article describes the antopometry study of dining chair and dining table furniture at the 4 Fingers Crispy Chicken restaurant located in Plaza Medan Fair building, Medan City, North Sumatra. Based on field observations, the dining table and dining chairs in that restaurant are uncomfortable when used in dining activities, so a deeper study of anthropometry and ergonomics is needed. The method used in this research is descriptive method with qualitative and quantitative data. Qualitative data is used to describe the mebel being studied, while quantitative data is used to process data taken from the distribution of questionnaires regarding the comfort level of customers who eat using the mebel. Literature studies on standard benchmarks for mebel sizes are also used to support and strengthen existing data. The results of this study indicate that the dining table and dining chairs used in the restaurant 4 Fingers Crispy Chicken do not meet antopometry and ergonomics standards so that customers feel uncomfortable when eating activities in the restaurant. Keywords: Anthropometry, Ergonomics, Chairs, Tables, Restaurant 4 fingers crispy chicken